A didactic intervention to strengthen critical thinking in the interpretation of visualized data - Lieb, Christiane; Pickhardt, Carola (Frontiers in Education, 2025)
BackgroundVisualized data are central to economic decision-making. A key educational challenge is fostering related competencies from school to higher education. Research on cognitive competencies and their assessment in data literacy remains scarce. This study examines the effects of an eight-week intervention based on a cognitive model, aiming to enhance learners’ critical engagement with and evaluation of visualized data.MethodsUsing a design-based research approach, a cognitive model was implemented as an instructional intervention and iteratively refined through multiple design cycles. A pre-post comparison was conducted within the experimental group (N = 40). The model emphasizes a backward-oriented interpretation of data visualizations, guiding learners from analysis to mental reconstruction of the underlying data structure and the data collection process. To enhance acceptance, learners were involved in model development from the outset.ResultsThere were changes in perceived ability to critically evaluate visualized data over time (p = 0.011, d = 1.72). In addition, the usefulness of the intervention is evaluated positively (M = 3.76, SD = 1.09). The model underwent several rounds of revision before being implemented in the main study during the winter 2025/26 as part of a statistics course for undergraduate students. These are therefore preliminary results in the context of this study.DiscussionTo our knowledge, this is the first instructional intervention based on a cognitive model to foster critical evaluation of visualized data. The backward-oriented approach guided learners’ step by step – from analyzing visualizations to mentally reconstructing the underlying data structure and drawing conclusions about the data collection process. Extending the intervention duration may further enhance its effectiveness. Overall, the cognitive-model-based intervention shows potential to improve data literacy competencies in higher education.